Concurrent validity and reliability of devices to measure jump height in men`s handball players - Soler-López, A.; García-de-Alcaraz, A.; Moreno-Villanueva, A.; Pino-Ortega, J. (Sensors, 2022)
Although there is a wide range of validated devices to measure vertical jump height, the degree of interchangeability among them is currently unknown. Aims: The purpose of this study was to examine the concurrent validity and reliability of multiple devices to measure jump height in men`s handball players. Methods: Sixteen players (age = 24.0 ± 3.7 years old) performed three types of jumps (n= 144—squat jump (SJ), countermovement jump (CMJ) and Abalakov jump (ABK)) on a contact platform (CHRONOJUMP®) while simultaneously being measured with two inertial devices (WIMU® and VERT®) and recorded with a high-speed camera. Vertical jump height was analyzed according to each type of jump. Results: The t-test showed statistically significant differences (p = 0.001) between the contact platform (reference standard) and the rest of the tools that tended to overestimate jump height in all jumps. SJ and CMJ proved to be the jump tests with the most stable reliability values in all devices (ICC: 0.92-0.98), except in the comparison with VERT®. Conclusions: Although all the analyzed devices proved to be valid and reliable in previous studies, they are not interchangeable. Therefore, it is suggested to always use the same type of device to evaluate vertical height jump.